Environmental Filtering Weakens Latitudinal Diversity Gradients in Soil Biodiversity Worldwide - Gui‐Feng Gao; Haiyan Chu; Teng Yang; Mingliang Ye; Xu Liu; Xiaofang Du; Luyao Song; Minyu Jing; Yuzhuo Zhao; Bin Ma; Jianming Xu; Nico Eisenhauer; et al. (Global Ecology and Biogeography, 2026)
Aims The latitudinal diversity gradient (LDG), a foundational pattern describing increasing biodiversity towards the Equator, has been extensively documented for aboveground organisms. However, whether this pattern holds for belowground biodiversity, the largest component of Earth's biodiversity remains unclear. Location Globe. Time Period Present. Major Taxa Studies Soil Archaea, Bacteria, Fungi, Protists, and Invertebrates. Methods We put together two data collections (amplicon and metagenomics) encompassing over 5,000 soil samples published online across multiple trophic levels, including archaea, bacteria, fungi, protists, and invertebrates. Results Our results demonstrate that multitrophic soil biodiversity deviates substantially from the classical LDG, with most taxa showing no decline in diversity with increasing latitude. We further found that local‐scale edaphic properties (e.g., soil carbon, nitrogen, and pH) and global‐scale climatic variables (e.g., rainfall and temperature), largely override latitude in explaining soil biodiversity variations. Multi‐group structural equation modelling indicated that local diversity was primarily governed by regional diversity and soil nitrogen availability, suggesting that nutrient supply mediates spatial variation in community assembly across regions. Conclusions Our findings challenge the universality of the classical LDG pattern and advance our understanding of the mechanisms shaping global soil biodiversity patterns.